The perturbation of PAHs on mosses in Aberdeen, Scotland, as a consequence of social restrictions imposed during the COVID-19 pandemic - Daniya, Thomas S.; Bowden, Stephen A. (Frontiers in Geochemistry, 2024)
Air quality and the concentration of PAH in urban environments is increasingly becoming a concern. Measuring air quality and PAH, and liking this to specific activities, requires deploying and recovering sampling devices to capture and measure any changes. From May 2020 to June 2021, during the "lockdown" period of the COVID-19 pandemic, acrocarpous and pleurocarpous mosses were collected from 5 types of site in Aberdeen, United Kingdom, and the concentration of PAH measured to track changes in PAH as travel related activities changed. The predominant types of PAH found on mosses were the 4 and 5 ring variety, with the 4 ring variety of PAH (medium molecular weight) becoming more dominant as the "lockdown" lifted. However, for most sites the concentration of PAH was evidently perturbed by the transient lifting, reimposing and then lifting of "lockdown" conditions, that either directly limited travel or changed the motivation for people to travel by car. Molecular diagnostic ratios or molecular marker parameters used to infer the source of PAH varied little and were nearly always consistent with PAH deriving from combustion in vehicle engines. Thus even when travel was limited, PAH still derived from vehicle usage, although the overall concentrations on mosses was much lower. On average the lowest concentrations of PAH were found on mosses collected from a recreational park located the furthest from traffic. The highest concentrations of PAH were observed on mosses collected from residential carparks during periods of time when the "lockdown" had been lifted. However, mosses from the same residential car parks had very low concentrations of PAH during periods of time with travel restrictions, strongly suggesting that for mosses local factors and patterns of vehicle usage strongly determine their exposure to PAH. Therefore, mosses within urban environments can be used for monthly monitoring of PAH as they are able to detect changes induced by human behavior.